Effects and safety of combined corneal collagen crosslinking and intrastromal corneal ring segment treatment in patients with keratoconus: a retrospective study - Dal, Ali; Canleblebici, Mehmet; Kutluksaman, Bunyamin; Erdag, Murat (Bmc, 2024)
Purpose To evaluate the safety and efficacy of different time-point combinations of intrastromal corneal ring segment (ICRS) implantation using femtosecond technology) and corneal collagen crosslinking (CXL) for the treatment of moderate-to-severe keratoconus (KCC). Methods This study included 69 eyes of 69 patients with keratoconus who underwent ICRS and CXL treatment at an Eye Hospital between March 2020 and March 2023. The patients were divided into two groups: Group 1 (n = 33 eyes of 33 patients), which received ICRS and CXL treatment in one session, and Group 2 (n = 36 eyes of 36 patients), which included treatment with ICRS for at least 6 months following CXL application. Preoperative and postoperative evaluations included visual acuity, autorefractometer refraction, corneal tomographic measurements using the Sirius (CSO) Scheimpflug camera and the TONOREF (TM) III device, and documentation of observed complications. Uncorrected visual acuity (UCVA) and best-corrected spectacle visual acuity (BCVA) were measured in each eye individually, and visual acuity was assessed using the logarithm of the minimum angle of resolution (logMAR). Results In Group 1, mean UCVA improved from 0.81 +/- 0.34 to 0.45 +/- 0.25 (p < 0.01), and mean BCVA improved from 0.76 +/- 0.35 to 0.38 +/- 0.20 (p < 0.01). In Group 2, mean UCVA improved from 0.71 +/- 0.32 to 0.43 +/- 0.30 (p < 0.01), and mean BCVA improved from 0.65 +/- 0.25 to 0.31 +/- 0.23 (p < 0.01). Both groups showed significant reductions in manifest spherical and cylindrical refraction (p < 0.01). Group 1 exhibited greater reductions in maximum keratometry (Kmax), flat keratometry (K1), steep keratometry (K2) (p < 0.05), and astigmatic aberration compared with group 2 (p < 0.01). The use of simultaneous or separate CXL and ICRS does not significantly increase the incidence of complications. Conclusions Both combined and separate CXL and ICRS treatments resulted in significant improvement in UCVA and BCVA and reduced manifest refraction. Although improvements were observed in groups 1 and 2 in terms of K1, K2, and Kmax at 6 months, the improvements were more pronounced in Group 1. These results highlight the potential benefits of simultaneous ICRS + CXL treatment and underscore the importance of optimising the timing of CXL treatment to achieve the best visual outcomes.
Keywords: Keratoconus; Corneal collagen crosslinking; Intrastromal corneal ring segments